Wybrane konsekwencje trafu moralnego dla etyki, koncepcji społecznych i religijnych - Strzyżyński, Przemysław (Teologia i Moralność, 2020)
The article presents the issue of moral luck and some of its consequences for the philosophy of law, social justice, political responsibility and some religious concepts. Recognition of the role of moral luck undermines the use of the concept of moral responsibility, guilt and merit. The consequences of recognizing that this challenge is justifi ed, reach those areas. They postulate, for example, the need to compensate social or property inequalities, insofar as they depend on the luck. Similarly, in the Christian concept of salvation as dependent off the will of God and man, there is the problem of the impact of luck. Release from moral responsibility for actions under the infl uence of luck, also puts into question the responsibility of politicians, whose decisions are often made in the absence of certainty.